The relationship between liquidity and profitability in the pharmaceutical industry a comparison between India and the United States - Vasconcelos, Maria Luís Bento de Almeida Aguiar de (2019)
This Work Project gives new insights into the liquidity and profitability relationship in the pharmaceutical industry, by adding epidemiological and economic variables to the debate. Between 2013 and 2017, the results show two significant relationships, positive in India, and negative in the United States (US). US producers are recommended to diversify and improve cost efficient processes, to decrease government dependency and increase customer reach. In Indian companies since working capital efficiency is a profitability driver, managers are recommended to sustain low production and skilled labour costs, and decrease cash conversion cycle and operating risk, while investing in marketing.